Community empowerment for diabetes mellitus awareness through the SAM MARIADI program in Malang City - Firdaus, Moh. Nur Cahyo; Ni'mah, Azizah Khoirotun; Sari, Putri Parmitha Dwi Kamala; Arum P, Nurul Iffah; Siswoyo, Berlyan Surya Pratama Putra; Ardiansyah, Fino; Aprilia, Risa; Prastiyo, M. Dodik; Meliza, Nur (Universitas Gadjah Mada, 2025)
Purpose: This study aimed to evaluate the impact of the SAM MARIADI (Sadar Diabetes Mellitus Mari Berdaya) program on improving knowledge and attitudes among the elderly in Bakalan Krajan Village, Malang City. Method: This quasi-experimental study involved 20 elderly participants with type 2 diabetes mellitus. The intervention consisted of educational and practical activities designed to promote awareness of and self-management for diabetes. Pre- and post-intervention assessments were conducted to measure changes in knowledge and attitudes. Results: There was a significant improvement in participants' knowledge and attitudes after participating in the SAM MARIADI program (p = 0.000). Before the intervention, only 20% of participants had good knowledge, which increased to 65% after the intervention. Those with poor knowledge decreased from 65% to 10%. Similarly, good attitudes have risen from 20% to 55%, and poor attitudes decreased from 60% to 10%. These results indicate that the program successfully enhanced awareness and behavioral readiness for diabetes self-management among the elderly. Conclusion: The SAM MARIADI program effectively improved knowledge and attitudes about diabetes management among the elderly, supporting its potential as a community-based health empowerment initiative aligned with the Sustainable Development Goals (SDGs).